Solikamsk magnesium works — launch padof innovations in Russia - D. L. Melnikov; A. V. Chub; D. V. Drobot (Тонкие химические технологии)
The article deals with the history of the production of rare earth elements (REE) in the Soviet Union, the changes that have occurred in connection with the collapse of the Union, the role of JSC "Solikamsk Magnesium Works" (JSC "SMW") in the rare metal industry today. It is shown that the introduction of chlorine processing method of loparite concentrate allowed to include in the work cycle about a quarter of the chlorine volume produced by the electrolysis of MgCl2 and laid the foundation for the economic sustainability of the enterprise. The prospects of the development of REE production in our country are scheduled.